2021
DOI: 10.1038/s41598-021-98935-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-phenotype genome-wide association studies of the Norfolk Island isolate implicate pleiotropic loci involved in chronic kidney disease

Abstract: Chronic kidney disease (CKD) is a persistent impairment of kidney function. Genome-wide association studies (GWAS) have revealed multiple genetic loci associated with CKD susceptibility but the complete genetic basis is not yet clear. Since CKD shares risk factors with cardiovascular diseases and diabetes, there may be pleiotropic loci at play but may go undetected when using single phenotype GWAS. Here, we used multi-phenotype GWAS in the Norfolk Island isolate (n = 380) to identify new loci associated with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…7 Previously, we employed principal component analysis (PCA) on multiple quantitative phenotypes associated with CKD, uncovering a novel susceptibility gene for kidney function that remained undetected in single-phenotype GWASs. 8 In this study, we introduce and implement a new approach termed combinatorial PCA to further investigate the genetic basis of CKD within the UK Biobank dataset. As a result, we identified a new locus, SH2B3 (SH2B adaptor protein 3), to be associated with CKD.…”
Section: Introductionmentioning
confidence: 99%
“…7 Previously, we employed principal component analysis (PCA) on multiple quantitative phenotypes associated with CKD, uncovering a novel susceptibility gene for kidney function that remained undetected in single-phenotype GWASs. 8 In this study, we introduce and implement a new approach termed combinatorial PCA to further investigate the genetic basis of CKD within the UK Biobank dataset. As a result, we identified a new locus, SH2B3 (SH2B adaptor protein 3), to be associated with CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney dysfunctions can be observed with increased levels serum levels of cystatin C, creatinine or urea. The best marker studied till date for CKD is GFR which is measured using exogenous markers or estimated (eGFR) depending on the concentrations of endogenous filtration markers of serum creatinine and cystatin C [6,7]. For the longer survival of the individual diagnosed with ESRD requires dialysis or a kidney transplant to maintain the survival of the patient [8].…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in the percentage of the disease numerous GWAS (Genome Wide Association Studies) have been conducted and many variants are identified in the last decade for CKD [7,[9][10][11][12]. This has also leaded to increase in testing out the different models of PRS (Polygenic Risk Score) for kidney risks in individual and in population cohort [13][14][15].…”
Section: Introductionmentioning
confidence: 99%